DNA methylation at LRP1 gene locus mediates the association between maternal total cholesterol changes in pregnancy and cord blood leptin levels. (22nd August 2020) - Guay, Simon-Pierre; Houde, Andrée-Anne; Breton, Edith; Baillargeon, Jean-Patrice; Perron, Patrice; Gaudet, Daniel; Hivert, Marie-France; Brisson, Diane; Bouchard, Luigi
Abstract: Placental lipids transfer is essential for optimal fetal development, and alterations of these mechanisms could lead to a higher risk of adverse birth outcomes. Low-density lipoprotein receptor ( LDLR ), LDL receptor-related protein 1 ( LRP1 ), and scavenger receptor class B type 1 ( SCARB1 ) genes are encoding lipoprotein receptors expressed in the placenta where they participate in cholesterol exchange from maternal to fetal circulation. The aim of this study was thus to investigate the association between maternal lipid changes occurring in pregnancy, placental DNA methylation (DNAm) variations at LDLR, LRP1, and SCARB1 gene loci, and newborn's anthropometric profile at birth. Sixty-nine normoglycemic women were followed from the first trimester of pregnancy until delivery. Placental DNAm was quantified at 43 Cytosine-phosphate-Guanines (CpGs) at LDLR, LRP1, and SCARB1 gene loci using pyrosequencing: 4 CpGs were retained for further analysis. Maternal clinical data were collected at each trimester of pregnancy. Newborns' data were collected from medical records. Statistical models included minimally newborn sex and gestational and maternal age. Maternal total cholesterol changes during pregnancy (ΔT3-T1) were correlated with DNAm variations at LDLR ( r = −0.32, p = 0.01) and LRP1 ( r = 0.34, p = 0.007). DNAm at these loci was also correlated with newborns' cord blood triglyceride and leptin levels. Mediation analysis supports a causal relationship between maternal cholesterol changes, DNAm levels at LRP1 locus, and cord blood leptin concentration ( p mediation = 0.02). These results suggest that LRP1 DNAm link maternal blood cholesterol changes in pregnancy and offspring adiposity at birth, which provide support for a better follow-up of blood lipids in pregnancy.